Mentalizing the patient–Patient experiences with short-term mentalization-based therapy for borderline personality disorder: A qualitative study - Hestbæk, Emilie; Hasselby-Andersen, Mathilde; Juul, Sophie; Beier, Nynne; Simonsen, Sebastian (Frontiers in Psychiatry, 2022)
Background: Mentalization-Based Therapy (MBT) is an evidence-supported psychotherapy approach for borderline personality disorder (BPD) that has been implemented in mental health services worldwide. Originally, MBT was developed as an 18-months program for BPD. However, a short-term (5 months) MBT program has been developed. Research into patient experiences with long-term MBT for BPD is scarce, and no studies have investigated patient experience with short-term MBT for BPD. Objective: The objective of this study was to explore patient experience with short-term MBT for BPD in the Danish mental health services. Methods: Semi-structured qualitative interviews were conducted with 12 outpatients diagnosed with BPD, who attended short-term MBT for 5 months. The interviews were verbatim transcribed and analyzed using thematic analysis with double coding. Results: The analysis resulted in four subordinate themes: 1) Treatment duration – too short or appropriately short?, 2) The group as a ‘safe space’, 3) Bad experiences impacted treatment negatively, and 4) My life has changed for the better. Conclusion: The results suggest that most of the patients were overall satisfied with short-term MBT, which they experienced as having a positive impact on their lives. However, a subgroup of patients wanted more therapy. This study highlighted the strengths and limitations of short-term MBT for BPD as experienced by the patients, and points to barriers in developing service-user informed short-term treatment options for BPD.